Phthalate Derivative from the Non-Polar Fraction of Andaliman (Zathoxylum acanthopodium DC.) Stem Wood from North Sumatra - Nuraini, Vidia Afina; Pratiwi, Eka Nikita; Musthapa, Iqbal (Jurnal Kartika Kimia, 2024)
Andaliman (Z. acanthopodium DC.), a plant belonging to the Zanthoxylum genus, is widely found in North Sumatra. Z. acanthopodium DC. has been traditionally used by local people to treat various diseases. Several secondary metabolites have been reported from the Zanthoxylum genus, including coumarins, flavonoids, lignans, terpenoids, steroids, amides, alkaloids, and phthalate derivatives. In this study, a phthalate derivative compound has been successfully isolated from the non-polar fraction of the stem wood of Z. acanthopodium DC., which was identified as di-(2-ethylhexyl) phthalate according to IR and NMR spectroscopic analyses.